High skin temperature and hypohydration impair aerobic performance - Sawka, M. N.; Cheuvront, S. N.; Kenefick, R. W. (Experimental Physiology, 2012)
This paper reviews the roles of hot skin (>35°C) and body water deficits (>2% body mass; hypohydration) in impairing submaximal aerobic performance. Hot skin is associated with high skin blood flow requirements and hypohydration is associated with reduced cardiac filling, both of which act to reduce aerobic reserve. In euhydrated subjects, hot skin alone (with a modest core temperature elevation) impairs submaximal aerobic performance. Conversely, aerobic performance is sustained with core temperatures >40°C if skin temperatures are cool-warm when euhydrated. No study has demonstrated that high core temperature (~40°C) alone, without coexisting hot skin, will impair aerobic performance. In hypohydrated subjects, aerobic performance begins to be impaired when skin temperatures exceed 27°C, and even warmer skin exacerbates the aerobic performance impairment (-1.5% for each 1°C skin temperature). We conclude that hot skin (high skin blood flow requirements from narrow skin temperature to core temperature gradients), not high core temperature, is the `primary' factor impairing aerobic exercise performance when euhydrated and that hypohydration exacerbates this effect.